Diversity and association analysis in bread wheat (Triticum aestivum L. em. Thell) under terminal heat stress condition - kumar, monu; Sharma, Ram Kumar (Journal of Cereal Research, 2018)
Studies on genetic diversity and interrelationship of yield and physiological traits were undertaken using 35 bread wheat genotypes under heat stressed environment. Significance of mean sum of square for genotypes suggested wide range of variability was exhibited for all the traits. Grain yield/square meter recorded highly significant positive genotypic correlation with biological yield and harvest index. Biological yield had positively significant correlation with number of effective tillers/m2 and harvest index had significantly positive correlation with 1000 grain weight. The path coefficient analysis carried out at genotypic level revealed that total chlorophyll content had maximum direct effect on grain yield followed by cartenoid content, harvest index, 1000 grain weight, and days to flowering, CTD and number of grains/spike. Therefore, for improving the grain yield of heat stresses conditions wheat, breeder should aim for selecting genotypes with higher harvest index, more numbers of spikes/plant, bold grains and higher amount of photosynthetic pigments. Â Based on D2 analysis 35 genotypes were grouped into 5 mlultigenotypic clusters. The distribution pattern of genotypes in different clusters was random. The highest number of genotypes was found in cluster III and IV whereas cluster II presented minimum number of genotypes. Highest inter cluster distance was observed between clusters III and IV and maximum intra cluster distance was observed in cluster III.